(untitled) (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The work is to analyze the range, classification, nomenclature, and advantages of modern synthetic and semi-synthetic gelling substances and prospects of using them in developing gels. Materials and Methods: We have used retrospective, logical, analytical, marketing, and economic research methods for the analysis of modern synthetic and semi-synthetic gelling substances. Results and Discussion: The detailed analysis of modern synthetic and semi-synthetic gelling substances most often used or promising in the development of cosmetics and medicines was carried out. Conclusions: The monitoring of gelling substances of semi-synthetic and synthetic origin demonstrated that the range of the accessory substance group allows to develop up-to-date cosmetic and pharmaceutical gels with satisfactory consuming, physicochemical, and rheological characteristics.